Fatal intrahepatic cholestasis - Gürgey, Aytemiz; Özsoylu, Şinasi; Koçak, Nurten (The Turkish Journal of Pediatrics, 1976)
Two cases of fatal intrahepatic cholestasis were presented, one of which was fatal. The possibility of one of the patient having Byler’s disease and the other, a variant of it was discussed.